College Students’ Perceptions of Stress and Coping Mechanisms (Journal of Education and Development, 2019)
Background: Typical college students experience stressors every day. Purpose: The purpose of this study was to determine college students’ perceptions of stress and coping mechanisms. Method: A quantitative, non-experimental, cross-sectional, descriptive research design was used to assess students’ perception of stress and coping mechanisms. To collect data, a survey tool was used to answer 6 demographic and twenty-five survey items on a 4-point Likert-type scale. Two central research questions guided the study: (1) What are college students’ perceptions of stress? and (2) What are college students’ perceptions of coping mechanisms? Results: The responses to these questions were analyzed and the implications are discussed. Conclusion: College students agree that college life is stressful and that their level of stress increases significantly before exams. In addition, students reported that expectations to excel in classes cause additional stress. Students reported a variety of coping mechanisms, including listening to music, socializing with friends/family, and sitting alone in a quiet place.